2004
DOI: 10.1007/s00038-004-3110-2
|View full text |Cite
|
Sign up to set email alerts
|

Research utilization and the impact of health promotion policy

Abstract: Research utilization is not supporting health promotion policy impact if political will is favorable, but if it is poor; political will itself is the crucial determinant of impact. The study contributes to the "research utilization"-field by showing that research utilization may partially compensate for lack of, rather than depend on, political will.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…15,16 A popular model of policy development developed by Richmond and Kotelchuck describes three interrelated factors that are thought to influence the development, implementation, and outcomes of policy: the knowledge base (research/ evidence), social strategy (effective interventions/solutions) and political will. 25 Recent studies from Europe suggest that research evidence can be an effective facilitator of policy implementation when political will is low. 25 When political will is high, evidence or effective interventions are less important to policy outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 A popular model of policy development developed by Richmond and Kotelchuck describes three interrelated factors that are thought to influence the development, implementation, and outcomes of policy: the knowledge base (research/ evidence), social strategy (effective interventions/solutions) and political will. 25 Recent studies from Europe suggest that research evidence can be an effective facilitator of policy implementation when political will is low. 25 When political will is high, evidence or effective interventions are less important to policy outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…25 Recent studies from Europe suggest that research evidence can be an effective facilitator of policy implementation when political will is low. 25 When political will is high, evidence or effective interventions are less important to policy outcomes. The growing body of empirical evidence and its synthesis through efforts such as the Community Guide bolster the knowledge base and suggest effective social strategies/interventions.…”
Section: Resultsmentioning
confidence: 99%
“…This is echoed by Lengerke et al. who analysed effective health promotion policy development across Europe and concluded that research evidence of effectiveness can be helpful when political will is low, but is less important when political will is high (36).…”
Section: Taking Policy Forwardmentioning
confidence: 99%
“…Finally, von Lengerke et al (2004) suggested that health promotion policy using public health research is associated with the policy's impact if both strong social strategies and the political will to support a given policy are present at the same time. To test this assumption, they analyzed data from a survey of policymakers concerning four prevention and health promotion policies in six European countries.…”
mentioning
confidence: 99%